Pengaruh Konsentrasi Minyak Atsiri Daun Kari (Murraya koenigii (L.) Spreng) dan Madu Terhadap Karakteristik Minuman Fungsional [The Effect of Curry Leaves (Murraya koenigii (L.) Spreng) Essential Oil and Honey Concentration on Characteristics of Functional Drink] - Siregar, Tagor M (FaST - Jurnal Sains dan Teknologi (Journal of Science and Technology), 2022)
Curry leaves have high content of flavonoids, alkaloids, terpenoids, and essential oils that have potential as antioxidants. The purpose of this study was to utilize the essential oil of curry leaves in the production of functional drink. In the preliminary stage, the hydrodistillation process, analysis of the physicochemical characteristics and antioxidant activity of the curry leaf essential oil were carried out. The main research was carried out by producing functional drinks with different concentrations of the essential oils of curry leaves (0.05%; 0.10%; 0.15%) and honey (5%; 10%; 15%). All formulations were tested for their sensory attributes (scoring and hedonic) and physicochemical properties (pH, total soluble solids, and color test). Based on GC-MS analysis, the chemical composition of the essential oils of curry leaves were Humulene (7.56%) and Î²-Phellandrene (3.80%) as antibacterial agents, whereas caryophyllene (20.45%), phytol (1.99%), Copaene (0.80%), and Î±-cubebene (0.29%) as antioxidants. Curry leaves produced essential oil with a yield of 0.44%, density of 0.9596 g/mL, clear yellow color, total phenolic content of 2.21±0.09 mg GAE/g, and antioxidant activity (RSA) of 77.95% at the concentration of 90000 ppm. The best formulation of functional drink was by the addition of essential oil of curry leaves at 0.05% and honey at 15% with resulted pH value of 6.03, total soluble solids of 12.03°Brix, Lightness of 53.91, °Hue of 87.98, and with overall acceptance at moderately like. The best functional drink had a total phenolic content of 4.13 mg GAE/L and antioxidant activity (RSA) of 79.41% at the concentration of 700000 ppm.Bahasa Indonesia Abstract:Daun kari (Murraya koenigii (L.) Spreng) memiliki kandungan flavonoid, alkaloid, terpenoid, dan minyak atsiri yang dapat dimanfaatkan sebagai antioksidan. Tujuan dari penelitian ini adalah untuk memanfaatkan minyak atsiri daun kari pada pembuatan minuman fungsional. Pada tahap pendahuluan dilakukan proses hidrodestilasi, analisis karakteristik fisikokimia dan aktivitas antioksidan minyak atsiri daun kari yang diperoleh. Pada tahap penelitian utama dilakukan pembuatan minuman fungsional dengan menggunakan konsentrasi minyak atsiri daun kari (0,05%; 0,10%; 0,15%) serta konsentrasi madu (5%; 10%; 15%). Seluruh formulasi minuman fungsional diuji sensori (skoring dan hedonik) dan fisikokimia (pH, uji total padatan terlarut, dan uji warna). Berdasarkan hasil analisis GC-MS, komposisi kimia minyak atsiri daun kari meliputi senyawa Humulene (7,56%) dan Î²-Phellandrene (3,80%) yang berfungsi sebagai antibakteri, sedangkan caryophyllene (20,45%), phytol (1,99%), Copaene (0,80%), dan Î±-cubebene (0,29%) berfungsi sebagai antioksidan. Minyak atsiri daun kari yang diperoleh memiliki rendemen 0,44%, berat jenis 0,9596 g/mL, warna kuning jernih, total fenolik 2,21±0,09 mg GAE/g, dan aktivitas antioksidan (RSA) 77,95% pada konsentrasi 90000 ppm. Minuman fungsional terpilih adalah minuman dengan konsentrasi minyak atsiri daun kari sebesar 0,05% dan konsentrasi madu sebesar 15% dengan pH 6,03, total padatan terlarut 12,03°Brix, Lightness 53,91, °Hue 87,98, nilai penerimaan keseluruhan agak suka. Minuman fungsional terpilih memiliki total fenolik sebesar 4,13 mg GAE/L dan aktivitas antioksidan (RSA) sebesar 79,41% pada konsentrasi 700.000 ppm.